2016
DOI: 10.1136/jclinpath-2016-203874
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive profiling of metaplastic breast carcinomas reveals frequent overexpression of programmed death-ligand 1

Abstract: AimsMetaplastic breast carcinoma (MBC) is a rare subtype of breast carcinoma less responsive to conventional chemotherapy than ductal carcinoma. In molecular terms, MBCs usually cluster with triple-negative breast cancers (TNBCs), but have a worse prognosis than TNBCs. Studies investigating MBCs for specific biomarkers of therapy response are rare and limited by the methodological approaches. The aim of the present study was to characterise MBCs on a molecular level and test programmed death-ligand 1 (PD-L1) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
101
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 30 publications
11
101
0
Order By: Relevance
“…A phase 1b trial has recently shown evidence of activity of pembrolizumab in heavily treated TN breast cancer [25]. A study that recently profiled 75 MBC tumors demonstrated significantly higher programmed death-ligand 1 expression (46%) in MBC compared with other breast cancer subtypes: HR positive (6%), HER2 positive (6%), triple negative breast cancer (TNBC) not otherwise specified (9%) [22]. This same review reported that tumor infiltrating lymphocytes varied greatly in MBC tumors.…”
Section: Discussionmentioning
confidence: 99%
“…A phase 1b trial has recently shown evidence of activity of pembrolizumab in heavily treated TN breast cancer [25]. A study that recently profiled 75 MBC tumors demonstrated significantly higher programmed death-ligand 1 expression (46%) in MBC compared with other breast cancer subtypes: HR positive (6%), HER2 positive (6%), triple negative breast cancer (TNBC) not otherwise specified (9%) [22]. This same review reported that tumor infiltrating lymphocytes varied greatly in MBC tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Adams et al . reported a remarkable response to combination therapy consisting of pembrolizumab and Nab‐paclitaxel in a patient with metaplastic breast cancer, associated commonly with over‐expression of PD‐L1 , as part of an ongoing clinical trial (http://clinicaltrials.gov identifier: NCT02752685).…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1 expression was associated with poor prognosis in a study conducted by Qin et al [28], who assessed correlations between PD-L1 expression and patient clinical characteristics in 870 breast cancer patients, and recently a clinical trial has assessed the safety profile and anti-tumour efficacy of pembrolizumab in triple-negative breast cancer patients that have shown acceptable safety and promising antitumour effects [29], with Phase II trials currently under way (clinicaltrials.gov identifier: NCT02447003). Additionally, Adams et al [30] reported a remarkable response to combination therapy consisting of pembrolizumab and Nab-paclitaxel in a patient with metaplastic breast cancer, associated commonly with over-expression of PD-L1 [31], as part of an ongoing clinical trial (clinicaltrials.gov identifier: NCT02752685).…”
Section: F -H -F -H + F + H + F + H -F -H -F -H + F + H + F + Hmentioning
confidence: 99%
“…Gene amplification of cyclin‐dependent kinase inhibitor 1B ( CDKN1B ) and fibroblast growth factor receptor 1 ( FGFR1 ) genes was detected in one case, each. These results indicate that PDCs exhibit significantly less targetable genetic alterations in contrast to related TNBC and metaplastic breast carcinomas . A single case with a mutation in BRCA1 gene indicates a potential benefit to platinum compounds and PARP inhibitors .…”
Section: A Summary Of the Molecular Profiling Results On Six Pleomorpmentioning
confidence: 83%